TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer's Disease - Valant, Valerie (2012)
Cerebral amyloid angiopathy (CAA) related intracerebral hemorrhage (ICH) is a devastating form of stroke with no known therapies. Clinical, neuropathological, and genetic studies have suggested both overlap and divergence between the pathogenesis of CAA and the biologically related condition of Alzheimer's disease (AD). Among the genetic loci associated with AD are APOE and TOMM40, a gene in close proximity to APOE. We investigate here whether variants within TOMM40 are associated with CAA-related ICH and CAA neuropathology. Using cohorts from the Massachusetts General Hospital (MGH) and the Alzheimer's Disease Neuroimaging Initiative (ADNI), we designed a comparative analysis of high-density SNP geno-type data for CAA-related ICH and AD. APOE ε4 was associated with CAA-related ICH and AD, while APOE ε2 was protective in AD but a risk factor for CAA. A total of 14 SNPs within TOMM40 were associated with AD (p< 0.05 after multiple testing correction), but not CAA-related ICH (all p>0.20); as a result, all AD-associated SNPs within TOMM40 showed heterogeneity of effect in CAA-related ICH (BD p<0.001). Analysis of CAA neuropathology in the Religious Orders Study (ROS) and Rush Memory and Aging Project (MAP), however, found that neuritic plaque, diffuse plaque burden, and vascular amyloid burden associated with all TOMM40 SNPs (p<0.02). These results suggest that alterations in TOMM40 can promote vascular as well as plaque amyloid deposition, but not the full pathogenic pathway leading to CAA-related ICH.